A Cross Sectional Study On The Evaluation Of Time Spent And Adherence For Selfcare Activities In Patients With Type II Diametes Mellitus And Its Correlation With The Glycemic Control - Sai Chandana Chiripireddy; Dharani Prasad P; Alok sachan; Tejaswini K; Maneesha P; Vishnu teja P; Sai Gowtham K; Sai Chaitanya K; Chandra Priya; Chandra Priya; Shaik Sumiya; Mallikarjuna B P (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Type 2 diabetes mellitus is a metabolic disorder that occurs when insulin resistance and eventual insulin deficiency lead to high blood glucose. DM was one of the most common disease in Endocrinology and Metabolism. Practical understanding of selfcare activities and glycemic control will advocate the appropriate treatment. The aim of our study was to evaluate the time spent and adherence for selfcare activities in patients with type 2 DM and its correlation with glycemic control in department of Endocrinology and Metabolism Sri Venkateshwara Institute of Medical Sciences south Indian tertiary care teaching hospital Tirupati Andhra Pradesh. A prospective observational study was conducted in 180 patients with type 2 DM. The data collected from 180 patients was initially assessed for their laboratory investigations, time spent and adherence for selfcare activities, prevalence of selfcare activities vs glycemic control